The circadian clock component BMAL1 regulates osteogenesis in osseointegration - Deng, Shiyong; Qi, Meiyao; Gong, Ping; Tan, Zhen (Frontiers in Pediatrics, 2022)
Congenital and developmental craniofacial deformities often cause bone defects, misalignment and soft tissue asymmetry, which can lead to facial function and morphologies abnormalities, especially among children born with cleft lip and palate. Joint efforts from Oral maxillofacial surgery, oral implantology and cosmetic surgery are often required for diagnosis and treatment. As one of the most widely performed treatment methods, implant-supported cranio-maxillofacial prostheses have been widely applied in the course of treatment. Therefore, stability of peri-implant bone tissue is crucial for the long-term success of treatment and patients’ life quality. The circadian clock component brain and muscle aryl hydrocarbon receptor nuclear translocator-like protein 1 (BMAL1) was found to be involved in the cell fate of bone marrow mesenchymal stem cells (BMSCs) which were essential in the fixation of titanium implants. This study aimed to investigate the effect of BAML1 on osteogenesis in osseointegration, providing a brand-new solution to increase bone-implant conjunction efficiency and implant stability, paving the way for a long-term satisfactory therapy outcome.